2021
DOI: 10.48550/arxiv.2111.15559
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scaling approach to nuclear structure in high-energy heavy-ion collisions

Abstract: In high-energy heavy-ion collisions, the energy density profile of the produced quark-gluon plasma and its space-time dynamics are sensitive to the shape and radial profiles of the nuclei, described by the collective nuclear structure parameters including quadrupole deformation β2, octupole deformation β3, radius R0 and surface diffuseness a. Using hydrodynamic model simulations, we find a general scaling relation between these parameters and a large class of experimental observables such as elliptic flow v2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 58 publications
(70 reference statements)
2
21
0
Order By: Relevance
“…We note, however, that almost all dependence is expected to cancel when taking the ratio between isobars that are as similar as 96 44 Ru and 96 40 Zr. All of our results agree qualitatively with AMPT studies [12,30] and as such our study is an important confirmation of those conclusions using a true hydrodynamic evolution. Nevertheless, we find that our v 3 {2} differs quantitatively.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…We note, however, that almost all dependence is expected to cancel when taking the ratio between isobars that are as similar as 96 44 Ru and 96 40 Zr. All of our results agree qualitatively with AMPT studies [12,30] and as such our study is an important confirmation of those conclusions using a true hydrodynamic evolution. Nevertheless, we find that our v 3 {2} differs quantitatively.…”
supporting
confidence: 92%
“…This could have been anticipated from nuclear structure analyses [9,10], though we note significant differences between studies. It is the purpose of this Letter to utilise these different studies in the state-of-the-art heavy ion code Trajectum and show how recent results from DFT can fully explain the STAR findings (see also [11,12] for a similar study using the transport model AMPT for v 2 and v 3 ).…”
mentioning
confidence: 99%
“…The Case 3 and Cases 7-10, skin-type and halo-type cases are taken from Xu's work [33] which considers the neutron-skin effect and/or a nuclear quadrupole deformity into the WS distribution with the TRENTO model. The Cases 4-6 are taken from Jia's recent researches [35,48], among which the Case 4 and Case 5 can well reproduce some experimental results. Meanwhile, the Case 6 is also from Ref.…”
Section: Introducing Geometry Configurations Of Isobar Nucleimentioning
confidence: 99%
“…It is worth noting that the Cases 4-6 and the effect of β 3 have been studied in detail in Refs. [35,48,51], and their recent study suggested that the ratios calculated at the same N ch provide a better baseline for the non-CME background [52]. For simplicity, we choose the halo-type neutron skin case for doing our following study related to the CME.…”
Section: Introducing Geometry Configurations Of Isobar Nucleimentioning
confidence: 99%
“…isobar baseline and background estimations. Theoretical model calculations[78][79][80][81][82][83][84][85][86][87][88][89][90] are necessary to understand above physics. Unlike RIBLL, FRIB and NICA at low and medium energies, isobar collisions open up new opportunity to study nuclear structure at a very short time scale (∼ 10 −23 s) through heavy-ion collisions.• One fundamental property of light atomic nuclei in unusual nuclear structure…”
mentioning
confidence: 99%